Synthesis of Pichromenes, a Potential Anticancer Agent Using Organocatalyst - Bôi, Lưu Văn; Thu, Phạm Hoài; Thành, Nguyễn Vũ Quang; Hồng, Doãn Thu; Ngọc, Nguyễn Bích; Huệ, Vũ Thị; Hùng, Mạc Đình; Weghe, P.Van De (VNU Journal of Science: Natural Sciences and Technology; Vol 29 No 4, 2013)
Abstract: Pichromene 1 is a potential anti-cancer substance that is being studied for treatment of chronic leukemia. In this paper have been developed method for synthesis of pichrmene 1 and its analogs by condensation between substituted salicylaldehyde and β -nitrostyrene derivatives under different conditions (solvent, reaction time, temperature and catalyst…). The research results showed that in toluene, at a temperature of 80 0 C, with acid L-pipecolic as catalyst, the yield of pichromenes reached 82% after 24h. The structure of the products was determined by the data of 1 H-NMR and 13 C-NMR spectroscopy.